PENERAPANSTRATEGI FLIPPED CLASSROOM DENGAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN MATEMATIKA DI KELAS XI SMKN 2 PADANGPANJANG - Eka Pasca Surya Bayu; Suci Mutia Rahmi (Inovasi Pendidikan, 2018)
Based on the results of interviews of researchers with teachers of mathematics subjects who teach class XI SMKN 2 Padangpanjang obtained information that student learning outcomes are still low. Factors that affect the low learning outcomes of mathematics learners are the level of understanding of learners on the basis of mathematics is still lacking. One way to solve this problem is to apply the Flipped Classroom Learning strategy with the Saintik Approach to Mathematics Learning.The purpose of this research is "To know the improvement of students' mathematics learning outcomes in the affective and psychomotor spheres after the implementation of the Flipped Classroom Learning Strategy with the Approach of Saintik in the class XI SMKN 2 Padangpanjang academic year 2017/2018". The learning result of the affective and psychomotor spheres experienced an increase in every meeting with very good category. The data analysis of the final test result is done using t-test. Based on the results of hypothesis testing for student learning outcomes in the cognitive domain, obtained t_hitung = 2.357> 1.67 = t _ ((0.05; 60)) then H_0 rejected. Based on this it can be concluded that the results of learning mathematics students who apply learning with Flipped Classroom Learning strategy with the approach of Saintik is better than the result of learning mathematics students without applying the strategy of Flipped Classroom Learning with the Approach of Saintik on students of class XI SMKN 2 Padangpanjang academic year 2017/2018. Keywords: Flipped Classroom, Learning Outcomes.